AUDIO VISUAL SEBAGAI MEDIA PENCEGAHAN HIPERTENSI PADA SISWA KELAS X (Jurnal Kesehatan Siliwangi, 2021)
Hypertension is a disease that can attack adolescents, which is based on the results of the publication of the National Health and Nutrition Examination Survey (NHANES) that 1 in 10 children aged 8-17 years has prehypertension and hypertension. This is because unhealthy behavior and lifestyle are factors for the onset of hypertension. Audio-visual media, especially animated videos, are used as a medium to add information and knowledge of adolescents about preventing hypertension. Research purposes This is Developing audio-visual health promotion media regarding the prevention of hypertension in adolescents. The research method uses the type of research is mixed methods with anresearch design exploratory sequential. The results of the study found that animated videos about hypertension prevention became the type of media that teenagers wanted to discuss material about preventing hypertension. The process of making media prototypes uses 3 stages of the ADDIE development model, namely Analysis, Design and Development. The validity of the audio-visual video animation media by material experts got a value of 97.89% and media experts got a score of 100% while the results of the validity of materials and media by students got a value of 88.08% which was included in the very feasible category. Further research is needed on the effectiveness of using animated video media.